1948
DOI: 10.1021/ie50464a019
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Monomeric and Polymeric Alkyl Acrylates and Methacrylates

Abstract: After an extended burial period of 13 weeks, the fabric lost only 31% of its strength. Under similar conditions of burial, the control lost 73 and 100%, respectively, of its initial strength.Results of the tests show that copper 8-quinolinolate-treated fabric gave excellent field performance in every respect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1953
1953
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(22 citation statements)
references
References 5 publications
2
20
0
Order By: Relevance
“…This effect is well known with the polyacrylates and polymethacrylates (27) (Figure 1), and is caused by lowering of the forces between the polymer chains owing to the bulkiness of the substituent groups. The reason for the minimum in the curve is that side chain crystallization occurs as the substituent chain increases beyond a certain length.…”
Section: Types Of Piasticizersmentioning
confidence: 66%
See 1 more Smart Citation
“…This effect is well known with the polyacrylates and polymethacrylates (27) (Figure 1), and is caused by lowering of the forces between the polymer chains owing to the bulkiness of the substituent groups. The reason for the minimum in the curve is that side chain crystallization occurs as the substituent chain increases beyond a certain length.…”
Section: Types Of Piasticizersmentioning
confidence: 66%
“…Figure L Brittle point of η-alkyl esters of polyacrylic and polymethacrylic acid (27) A distinction should be made between solvent piasticizers and nonsolvent piasticizers. With an amorphous polymer, any plasticizer is a solvent plasticizeri.e., under suitable conditions the polymer would eventually dissolve in the plasti cizer.…”
Section: Number Of C Atoms In Alkyl Residuementioning
confidence: 99%
“…The apparent viscosity at thermal equilibrium is given by, Equations (9) and (10) give the temperature rise at the bob and apparent viscosity, respectively, at thermal equilibrium. The problem of the transient behavior, or time dependence of viscosity is considerably more difficult, however, the relaxation time may be estimated fron the time constant for thermal equilibrium.…”
Section: P -mentioning
confidence: 99%
“…Rehberg and Fisher studied the brittle points of polyacrylates and poly(methacrylates) and found that upon an increase in carbons within the alkyl side chain the brittle points decrease up to 8 carbons for acrylates and 12 carbons for methacrylates, above which the brittle points increased. 13 This was attributed to the increase in the melting point of the side chains 14,15 Jordan et al investigated the crystallinity of the alkyl side chains in poly(n-alkyl acrylates) and they established that only the outer methylene units contributed to the crystal lattice. 16,17 This was also independently confirmed by several other investigators, it was proposed that the 8-9 methylene units closest to the polymer backbone do not contribute to the side chain crystallinity.…”
Section: Introductionmentioning
confidence: 99%